Homologous recombination deficiency in triple negative breast cancer. (June 2019) - Belli, Carmen; Duso, Bruno Achutti; Ferraro, Emanuela; Curigliano, Giuseppe
Abstract: Triple negative breast cancer (TNBC) represents a heterogeneous subtype of breast cancer characterized by an unfavorable prognosis due to its aggressive biology. The median overall survival (OS) for patients with metastatic TNBC is around 9–12 months with conventional cytotoxic agents. Considering this suboptimal outcome, which is induced despite of medical treatment, new therapeutic strategies would be urgently needed. The ultimate goal of precision medicine is to identify specific molecular alterations that permit considering effective targeted drug(s). Germline BRCA mutations occur in 10–20% of TNBC patients while somatic mutations occur in 3–5% of them. Alterations in the homologous recombination (HR) system are typical of BRCA mutant tumors, but can also be identified in tumors that do not carry this mutation, defining a subgroup of patients referred to as BRCAness. In this review, we focus on the role of homologous recombination deficiency (HRD) as both predictive and prognostic factor in different settings of TNBC patients treated with DNA damaging drugs and poly ADP ribose polymerase (PARP) inhibitors. Highlights: Data from The Cancer Genome Atlas identified germline BRCA1/2 deleterious mutations in 10–20% of TNBC while somatic mutation in 3–5% of them. Alterations in the HR system, typical of BRCA mutant tumors, can be also identified in tumors not carrying this mutation, defined as BRCAness. Combination of loss of heterozygosity (LOH), telomeric allelic imbalance (TAI), and large-scale transition (LST) define the HRD score. An HRD score ≥42 or the presence of BRCA1/2 mutations were correlated with objective response to cisplatin. HRD has a potential role as a biomarker to predict response to DNA damaging drugs, PARP inhibitors, anthracyclines and/or cyclophosphamide.